Sistem Pakar dalam Menganalisis Gangguan Jiwa Menggunakan Metode Certainty Factor - Rafi Septiawan Putra; Y Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2021)
People with Mental Disorders (ODGJ) as a trigger for people who suffer from disorders of thought, feeling and behavior cause changes in attitudes and behavior that hinder normal human functioning. Mental disorders as a syndrome characterized by a change in a person's behavior that will be associated with symptoms such as difficulties or disorders, as well as psychological functions and behavior that are not confident in dealing with people but can also be with that person. An expert system is an intelligent computer technology that is based on solving problems using inferential knowledge and procedures. As a problem solver, expert systems will also find it easier to make decisions or policies like humans do. This study aims to produce an expert system that is used to analyze mental disorders who can make similar decisions, as well as psychiatric specialists. The data processed in this study is scientific data on mental disorders ranging from types of mental illness, early symptoms of disease and patient diagnosis data by mental health specialists, then the data is processed using the Certainty Factor method and displayed in the form of a web-based application using the PHP programming language. and MySQL databases. The results obtained from testing the expert system using the Certainty Factor method show that there is a match between the results of an expert diagnosis of depression with a certainty level of 73%. An expert system for analyzing mental disorders using the Certainty Factor method can make it easier for sufferers to understand the type of mental disorder they are experiencing.